DESCRIPTION AND COMPARISON OF SELECTED PLATFORMS FOR THE IMPLEMENTATION OF ONLINE LEARNING ACTIVITIES - Milan, KLEMENT; NEMEC, Daniel (Trends in education, 2023)
In view of the pandemic situation, many educational institutions are forced to supplement classical teaching with online activities. The choice of the appropriate technical means, whether in the form of an LMS (e.g. Moodle) or communication platforms with the possibility of sharing learning materials (e.g. MS Teams), is largely up to the choice of the respective educational institution. The latter is often faced with a difficult choice, as the market offer of such applications and systems is wide and it is not easy to find the most suitable tool to suit all needs. For this reason, this paper has been written to describe the main characteristics and features of selected platforms for supporting online educational activities that are currently available on the Czech market. This description includes their comparison and identification of the main benefits or negatives of each platform, in order to facilitate the orientation of future users who are considering their deployment.
Keywords: E-learning; on-line education; on-line learning activities; on-line learning environments.